PERFORMA PENCAHAYAAN ALAMI RUANG KELAS SEKOLAH DI KOTA PONTIANAK - lestari lestari; Muhammad Ridha Alhamdani; syaiful muazir; Muhammad Nurhamsyah; adilla chairiah (Jurnal Arsitektur ARCADE, 2023)
The visual comfort of classrooms in schools can be increased through proper lighting so that it can have a positive effect on student learning activities. The quality of lighting in school classrooms can be achieved by maximizing natural lighting, which can contribute to the health, comfort and productivity of students in addition to reducing operational costs. The performance of natural lighting that occurs in schools is important to know, especially in areas with potential natural lighting such as in Pontianak City, so that it can be considered in the design of school buildings in the future.This paper aims to provide results of natural lighting performance in classrooms in several school buildings in Pontianak City. The study was conducted on 4 school buildings in Pontianak City using direct measurements reinforced by simulation. The results showed that most of the natural lighting of the classrooms had met the requirements needed for teaching and learning activities, especially in sunny weather conditions. However, there is a risk of glare in the seating area on the side next to the window. Cloudy weather conditions also show the DF value which is at 1-1.5% so that the utilization of natural lighting in these conditions is not optimal.